SIGI TENTANG PENGGUNAAN ALAT EVALUASI PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 3 JOMBANG - GRESSI ACHDIA SEPTIA PRADANA (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
Problems of education in Indonesia, one of which is the poor quality of teachers in their role. An important role of the teacher is doing evaluation processes on students. The instruments used in the process of evaluation is the evaluation tools. The purpose of this study is to know the evaluation tools used in SMA Negeri 3 Jombang such as its kind and its appropriateness. Besides, it is also to know how the students’ attitude and response toward the use and the implementation of the evaluation tools itself. This research is a descriptive study. Based on the results of the research it is known that The accounting teacher in SMA Negeri 3 Jombang used the evaluation tools in the form of essay and multiple choice tests. Feasibility of qualitatively showed that very decent. Quantitatively, Paket B has higher validity, reliability, level of difficulty and discrimination than Paket A.. From the observation during the evaluation, the students are calm and honest from the first until the third evaluation. The students’ response toward the implementation of the evaluation tools itself is very good. Key words: Evaluation Tools